PENGAWAS SEKOLAH SEBAGAI SUPERVISOR - Wena Fitra Ayudia; Wieke Junianti D; Yola Marselina; Jamilus Jamilus; Anis Mahatika (JIP: Jurnal Ilmu Pendidikan, 2024)
the school supervisor plays a crucial role in improving the quality of education in a school. As a supervisor responsible for overseeing, guiding, and providing support to educators and education staff, the school supervisor functions as an agent of change that motivates continuous improvement. The school supervisor acts as a facilitator in the professional development of teachers, analyzes the learning process, and provides constructive feedback for the improvement of the learning process. In addition, the school supervisor also plays a role in designing and implementing educational policies relevant to the needs of the school, ensuring, that the established educational standards are achieved optimally and effectively. Through their role as a supervisor, school supervisor are expected to create a more efficient, effective, and innovative educational environment to achieve national educational goals.